2001
DOI: 10.1053/jhep.2001.29201
|View full text |Cite
|
Sign up to set email alerts
|

The influence of human immunodeficiency virus coinfection on chronic hepatitis C in injection drug users: A long-term retrospective cohort study

Abstract: In this study we analyzed the influence of human immunodeficiency virus (HIV) infection on the course of chronic hepatitis C through multivariate analysis including age, alcohol consumption, immune status, and hepatitis C virus (HCV)-related virologic factors. Eighty HIV-positive and 80 HIV-negative injection drug users included between 1980 and 1995 were matched according to age, gender, and duration of HCV infection and followed-up during 52 months. The progression to cirrhosis was the primary outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
183
4
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(208 citation statements)
references
References 43 publications
(50 reference statements)
12
183
4
8
Order By: Relevance
“…83,100,101 Studies have shown that chronic hepatitis C patients with HIV infection have a worse prognosis as compared to those without HIV. [102][103][104][105][106][107] Coinfection with HIV and HCV is associated with a lower rate of spontaneous HCV RNA clearance. 108 There is an increased rate of fibrosis in HIV and HCV coinfected patients, with an accelerated progression of HCV-related liver disease.…”
Section: Management Of Hcv In Hiv Coinfectionmentioning
confidence: 99%
“…83,100,101 Studies have shown that chronic hepatitis C patients with HIV infection have a worse prognosis as compared to those without HIV. [102][103][104][105][106][107] Coinfection with HIV and HCV is associated with a lower rate of spontaneous HCV RNA clearance. 108 There is an increased rate of fibrosis in HIV and HCV coinfected patients, with an accelerated progression of HCV-related liver disease.…”
Section: Management Of Hcv In Hiv Coinfectionmentioning
confidence: 99%
“…Several studies conducted before the introduction of highly active antiretroviral therapy (HAART) have suggested that HIV infection changes the natural history of HCV infection, leading to more rapid progression of liver fibrosis (9,(23)(24)(25)(26)(27)(28). The progression, which typically takes 30 years or more in patients infected with HCV, could take less than half this time in co-infected patients (12).…”
Section: Introductionmentioning
confidence: 99%
“…Em outros estudos que avaliaram o tratamento de pacientes co-infectados, os valores médios foram semelhantes, variando de 478 (20) a 500 (5,7) células/mm 3 , sendo maiores que o observado na presente série. No entanto, em outros trabalhos que não incluíram apenas pacientes candidatos ao tratamento anti-VHC, a contagem média de células CD4 foi inferior à observada nesta casuística (12,31) .…”
Section: Discussionunclassified